Prawna ochrona rodziny w sytuacji stanu nadzwyczajnego: [Legal protection of family in state of emergency] (Studia Prawnicze / The Legal Studies, 2007)
Stan nadzwyczajny, nawet jeśli nie przybiera formy konfliktu zbrojnego, stawia cały naród w obliczu szczególnego zagrożenia, wstrząsa wszelkimi strukturami państwa i społeczeństwa, w tym również najmniejszymi, tj. rodzinami. Niekiedy istniejąca sytuacja rodzi konieczność podjęcia przez państwo szczególnych środków i działań wymagających niejednokrotnie „zawieszenia” określonych praw zagwarantowanych jednostce ludzkiej w poszczególnych traktatach ochrony praw człowieka i dlatego też dokumenty te przewidują możliwość „uchylenia - w ramach derogacji zobowiązań państwa w zakresie ochrony praw człowieka wynikających z danego aktu.Wobec machiny państwa i derogacji stoi rodzina, podstawowa komórka społeczeństwa, środowisko życia jednostki ludzkiej, choć niewielka, ale o fundamentalnej roli w społeczeństwie. Pojawia się zatem pytanie o stopień ochrony przynależnej rodzinie na wypadek zaistnienia „niebezpieczeństwa zagrażającego życiu narodu” oraz zakres dopuszczalnej ingerencji w te prawa w razie skorzystania przez państwo ze wspomnianego mechanizmu derogacji. Czy brak zamieszczenia expressis verbis praw rodziny w katalogu praw niederogowalnych czyni prawa te bezbronnymi, pozbawionymi ochrony i gwarancji prawnych oraz pozostawionymi „na łasce” władz państwowych?Celem tego artykułu będzie właśnie zbadanie i ocena stanu ochrony prawnej zagwarantowanej rodzinie na wypadek stanu nadzwyczajnego w międzynarodowych instrumentach ochrony praw człowieka oraz międzynarodowego prawa humanitarnego. Ośmielam się wręcz postawić - a raczej podtrzymać postawioną przez prof. Tadeusza Jasudowicza - tezę o niewzruszalności tego odcinka sub stancji praw człowieka w kontekście derogacji, pomimo braku odnośnych norm w katalogach praw niederogowalnych występujących w prawie międzynarodowym praw człowieka, oraz podjąć próbę zebrania argumentów za nią przemawiających. This study is aimed at analysing the issue of family's legał protection in State of emergency. This problem is emerging in exceptional situations due to the fact that nonę of human rights treaties (apart from the American Convention of Human Rights) includes family's rights in catalogues of non-derogable ones.In the first part of this work, I have tried to introduce the mechanism of derogation of human rights obligations under the State of emergency (with some description of its structural elements) and make a thesis statement of non-derogable naturę of family unit's rights despite of its lack in intemationally recognized catalogues of non-derogable rights.The second part of this study contains presentation of reasons that lie behind the thesis stated above, starting with arguments derived from implications of rigorous conditions of derogation clause (with special regards to substential tests embodied in it which significantly restrict the possibility of derogation from family rights guaranteed in human rights intruments). Then we have tackled with theprinciple of consistency reąuiring that derogating measures are“not inconsistent with their [e.i. State's] other obligations under International law” what opens the doors to many normative areas of guarantees for family protection prescribed in different intemational law sources, with special emphasis lied on intemational humanitarian law, customary law and ius cogens. We ended with argumentation conseąuent the generał theory and philosophy of human rights law and implications of special protection given to children and some categories od women. And least but not last, we examine the way domestis legał regimes influence the scope of permissible derogation, with remarks being madę on the basis of the Polish Constitution of 1997 (supllemented with a short review of other countries' constitional provisions).In the next part we have faced the problem of relevance of legał obligations under intemational humanitarian law in the State of emergency which is not an armed conflict.An attention was paid to if and to what extent ąuarantees provided in the Geneva Conventions of 1949 and Additional Protocols of 1977 narrow the scope of authorities' discretion in undertaking mesuares derogating from obligation to repect standards of protection of particular human rights (including these of families).Further, we have tum to the underlining the need for improving the normative regulation of rights of the family in case of proclaiming the State of emergency and covering with precisely stipuleted guarantees “the gray zonę between war and peace”, e.i. process of elaborating “minimum humanitarian standards” (lately called as “fundamental standards of hu anity”) to see what protection of family unit they anticipate. Some remarks have also been madę upon activities undertaking by th  Intemational Committee of the Red Cross on behalf of families and their particular members in times of emergency situations.In conclusion, presented in this study fortress of guarantees on behalf of legał protection of family and its rights in times of State of emergency which is not an armed conflict shows on the one hand a wealth of sources we can derive arguments for demostrating constraints of taking derogating measures from human rights obligations (including family's right to protection) under the State of emergency, but on the other, it also reveals the weakness of this legał reasoning and some kind of uncertainty so dangerous when human rights protection must to surmount the most exceptional conditions.